Neo-Schumpeterian Knowledge Funnel and Foresight Project Development in the System of Establishing Stability of the Competitive Advantages of Enterprises - DUDIN, Mihail Nikolaevich; SEPIASHVILI, Ekaterina Nikolaevna; SMIRNOVA, Olga Olegovna; FROLOVA, Еvgenia Еvgenevna; VOYKOVA, Natalia Andreevna (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
This article aims at presentation of contemporary approaches to ensuring the competitiveness of enterprises in the conditions of turbulent change and against the background of the increasing influence of the knowledge (cognitive) factors. The key task of the present article is to develop the concept of ensuring the enterprise competitiveness through the use of Neo-Schumpeterian Knowledge Funnel and foresight project development of the future of the enterprises, taking into account global unchanging sociopolitical, economic and technological trends. During the presentation of the work, the following conclusions were obtained:  Ability of enterprises to compete in the market depends on a number of factors and conditions; the unique (hardly copyable or uncopyable) competitive advantages / core competencies play a major role in ensuring the competitiveness of enterprises. The accumulation of the knowledge capacity of the enterprise development promotes their innovative activity, i.e. ability to create and offer high-tech products (goods, works, services) to the market;  Competitive potential of enterprises based on knowledge is implemented due to the use of a funnel of emerging opportunities – the neo-Schumpeterian funnel. This funnel allows converting the potential growth and development gained by the firm into sustainable economic benefits that are unavailable to competitors. The constant increase in economic benefits for enterprises through innovation activity and intensive use of knowledge can be seen as a Schumpeterian rent;  Planning of the competitive and sustainable development of enterprises determined by the use of cognitive resources and the growth of innovative activity is advisable to base on foresight technology (technology of foresight project development).triple helix model (universities-state-business).In relation to the banking sector, adaptation of the triple helix model means reforming the tripartite institutional interaction by replacement of the real sector with the banking sector, and the public sector – with central bank and the macroprudential oversight bodies.
Keywords: Neo-Schumpeterian Knowledge Funnel; competitive advantage; sustainable development